Rural families’ at-home STEM tinkering stimulates creativity, self-expression, and social–emotional engagement - Gutierrez, Kristie S.; Swanson, Kylie J.; Blanchard, Margaret R. (Frontiers in Education, 2025)
IntroductionInformal STEM learning experiences include visits to museums, zoos, and aquariums, as well as experiments and other activities performed at home. Family involvement in these experiences has been linked to increased student interest and participation in STEM fields; yet, scant research has been conducted on at-home STEM.MethodsThis descriptive case study investigated the tinkering experiences of nine rural middle school students and their families who participated in a series of interactive, at-home activities. The overarching research question was: In what ways do families engage in at-home STEM interventions? The Learning Dimensions of Making & Tinkering framework guided data analyses of at-home audio recordings. Follow-up interviews with families about their informal STEM experiences were a secondary data source used to contextualize family dynamics.ResultsOverall, families who engaged in at-home STEM activities were most likely to demonstrate Social & Emotional Engagement (e.g., Collaborating and Working in Teams) and Creativity & Self-Expression (e.g., Expressing Joy and Delight), and were least likely to exhibit Initiative & Intentionality. Engagement patterns differed based on family (dynamics and backgrounds), family participant group type (number of parents and children in groups), and the STEM activity. Rich descriptions and vignettes illustrate the moment-to-moment experiences of families as they engaged in at-home STEM together. Additional evidence was gleaned through family interviews. Families valued their time together and tinkered in ways that stimulated their self-expression, creativity, and social and emotional skills.DiscussionRecommendations for professional developers include attention to the order of activity difficulty, length of time required, inclusion of conceptual material, and allowing time for failure and risk-taking. Researcher recommendations suggest ways to streamline the data collection and analyses to ease the resources required to study other populations of interest.